Lizzie flying solo - Steveson, Nanci Turner (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
Hoping to go unnoticed while living in a shelter after her father is arrested, Lizzie St. Clair bonds with a frightened pony at a local stable while struggling to accept help from new friends.
Keywords: White collar crimes -- Fiction; Emergency housing -- Fiction; Family problems -- Fiction; Ponies -- Fiction; White collar crimes -- Fiction; Family life -- Fiction; Ponies -- Fiction